Reformasi Hukum Pidana Berbasis Pluralisme: Pengakuan Hukum Adat dalam Sistem Peradilan Indonesia - Syifa Khusnul Hijriyah; Hana Faridah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Criminal law reform based on pluralism in Indonesia marks a significant shift in the criminal justice system by recognizing the existence of customary law as a living law within society. This recognition is reflected in the new Criminal Code, which emphasizes the synergy between national criminal law and customary criminal law, thereby strengthening legal pluralism in Indonesia. The integration of customary law into the criminal justice system not only enriches case resolution approaches through restorative justice values and local wisdom but also maintains harmony between national and local legal systems. However, this recognition also presents challenges, particularly regarding legal certainty and the principle of legality, as customary law is often unwritten and varies across regions. Therefore, harmonization mechanisms and additional regulations are needed to ensure balanced and fair integration. Pluralism-based criminal law reform that accommodates customary law aims to create an inclusive criminal justice system, responsive to community needs, and aligned with Pancasila values as the nation's foundation.